Phenylboronic Acid as Efficient and Eco-Friendly Catalyst for the One-Pot, Three-Component Synthesis of α-Aminophosphonates under Solvent-Free Conditions - Tibhe, Gaurao D.; Bedolla-Medrano, Mercedes; Cativiela, Carlos; Ordóñez, Mario (Synlett, 2012)
A simple, mild, and efficient one-pot, three-component synthetic method has been developed for the preparation of α-aminophosphonates using phenylboronic acid as catalyst under solvent-free conditions at 50 °C. The process involves the reaction of carbonyl compounds (aldehydes or ketones) with benzylamine and dimethyl phosphite. A wide range of carbonyl compounds are compatible with this reaction, producing tertiary and quaternary α-aminophosphonates in moderated to excellent yields in short time.
Keywords: α-aminophosphonates; one-pot three-component reaction; phenylboronic acid; solvent-free conditions